Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1128/aac.00943-16
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Resistance to Clarithromycin in Mycobacterium abscessus Subspecies

Abstract: Mycobacterium abscessus is an emerging pathogen against which clarithromycin is the main drug used. Clinical failures are commonly observed and were first attributed to acquired mutations in rrl encoding 23S rRNA but were then attributed to the intrinsic production of the erm(41) 23S RNA methylase. Since strains of M. abscessus were recently distributed into subspecies and erm(41) sequevars, we investigated acquired clarithromycin resistance mechanisms in mutants selected in vitro from four representative stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 47 publications
(69 reference statements)
3
57
1
1
Order By: Relevance
“…The frequencies of mutations at position 2058 or 2059 differ between studies. Some studies showed that the majority of mutational changes involved A2059 (17,29), whereas other studies found that most mutations involved A2058 (18,30). In our study, 23% involved A2059, with the remaining 77% involving A2058, and there was no difference in clarithromycin MICs based on mutation position, although only small numbers of isolates were studied.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The frequencies of mutations at position 2058 or 2059 differ between studies. Some studies showed that the majority of mutational changes involved A2059 (17,29), whereas other studies found that most mutations involved A2058 (18,30). In our study, 23% involved A2059, with the remaining 77% involving A2058, and there was no difference in clarithromycin MICs based on mutation position, although only small numbers of isolates were studied.…”
Section: Discussioncontrasting
confidence: 63%
“…In our study, of the 13 isolates with rrl mutations, 85% had the T28 sequevar and 15% had the C28 sequevar of erm(41). A recent study of mutants selected in vitro for acquired macrolide resistance found that only 19% of mutants derived from the T28 sequevar had rrl mutations, whereas 100% of mutants derived from the C28 sequevar had rrl mutations (29). In clinical isolates, rrl mutations were observed more frequently in isolates of the T28 sequevar than in isolates of the C28 sequevar (18,30).…”
Section: Discussionmentioning
confidence: 99%
“…Mougari and colleagues found that in 39/40 M. abscessus subsp. massiliense isolates selected for clarithromycin resistance, this could be explained by an rrl mutation at positions 2270 and 2271, with a further sample containing an rplV insertion (20). All of our isolates contained this insertion (which was also present in the reference sequence with GenBank accession number NC_010397.1), which was associated with susceptibility to clarithromycin, except in the presence of a relevant rrl mutation.…”
Section: Discussionmentioning
confidence: 74%
“…Clarithromycin (41) were detected in this study; however, numerous studies have revealed that both resistance mechanisms can occur concurrently (36,38), and that a functional erm(41) gene does not exclude selection for rrl mutations (44). Transcriptome analysis of M. abscessus complex revealed the presence of several novel open reading frames, which could be activated by stressful conditions, such as hypoxia, to persist (45).…”
Section: Amikacinmentioning
confidence: 56%
“…Conversely, several studies have reported on acquired resistance due to rrl mutations in the absence of any macrolide exposure (16,37). However, an in vitro study reported that rrl mutations at position 2058 or 2059 were observed during incubation with clarithromycin (38). In East Asia, low dose macrolides are often administered for prolonged periods to treat chronic respiratory disorders, such as diffuse panbronchiolitis, to stimulate an immunomodulatory effect (39).…”
Section: Discussionmentioning
confidence: 99%